Comet assay as a human biomonitoring tool: application in occupational exposure to antineoplastic drugs - Ladeira, Carina (2015)
Antineoplastic drugs are a heterogeneous group of chemicals used in the treatment of cancer, and have been proved by IARC to be mutagens, carcinogens and teratogens agents. In general, chemicals that interact directly with DNA by biding covalently or by intercalating, or indirectly by interfering with DNA synthesis, were among the first chemotherapeutics developed. Also, these drugs can induce reactive oxygen species that can lead to DNA damage and, consequently, mutations. These drugs are often used in combination to achieve synergistic effects on tumour cells resulting from their differing modes of action. However, most if not all of these chemical agents are generally nonselective and, along with tumour cells, normal cells may undergo cytotoxic/genotoxic damage. The in vivo exposure to antineoplastic drugs has been shown to induce different types of lesions in DNA, depending on the particular stage of cell cycle at the time of treatment. Besides the patients that use these drugs as a treatment, workers that handle and/or administer these drugs can be exposed to these substances; namely pharmacy, and nursing personnel in hospital context.